P328Satisfaction towards clinical training and academic activities among residents and early-career cardiologists. (18th June 2020) - Nesti, M; Tola, G; Brunacci, M; Santobuono, V E; Dendramis, G; Picciolo, G; Lucciola, M T; Russo, V
Abstract: Background: Because of the progress in diagnostic and therapeutic cardiovascular disease, the skills to be acquired during fellowship training has increased significantly. In particular, the evolution in arrhythmology and electrophysiology was fast in the last years. This could have created a gap between the training program during the fellowship and the new technologies, growing demand for re-defined educational requirements to ensure uniformity of knowledge and competence of those practicing in electrophysiology. Purpose: The AIAC (Italian Association of Arrhythmology and Cardiostimulation) Young Pacing committee conducted a survey to obtain information the satisfaction on the educational and training obtained during the residency course by residents and young cardiologists (arbitrarily defined as age ≤ 40 years). Methods: The survey was conducted from January to May 2019. Residents and young cardiologists were contacted to complete the survey by e-mail. They were asked to answer a questionnaire containing information about scholarly activity included satisfaction of educational and clinical proficiency in arrhythmology and electrophysiology and educational in electrophysiology after the residency. Results: We obtained 334 answers to the survey. One hundred forty-six individuals (43.7%) were residents and 188 (56.2%) were young cardiologist. In Electrophysiology Department, 3-6 months were dedicated to Clinical Arrhythmology for 135 partecipants (40.4%), 1-2 months to cardiac pacing for 132 partecipants (39.5%) and 1-2 months to EP Lab for 139 partecipants (41.6%). Three hundred twenty-nine people responded to questions about satisfaction in educational. In terms of educational in Clinical Arrhythmology, 100 responders (30.4%) were "very satisfied", 105 (31.9%) were "satisfied" and 124 (37.7%) were "dissatisfied". About Cardiac Pacing, 84 responders (25.5%) were "very satisfied", 93 (28.3%) were "satisfied" and 152 (46.2%) were "dissatisfied". Only 51 (15.5%) participants were "very satisfied" with their training in Electrophysiology, whereas 81 (24.6%) were "satisfied" and 197 (59.9%) were "dissatisfied". About self-assessed clinical proficiency in Arrhythmology at the end of fellowship, 30 responders (9%) defined themselves as completely confident in Clinical Arrhythmology, 126 (37.7%) in Ambulatory Electrophysiology (ECG Holter and device check), 28 (8.4%) in cardiac pacing, 10 (3%) in performing electrophysiological study and nobody in catheter ablation. One hundred twenty-one (36.8%) participants improved their competence in Cardiac Arrhythmia Management attending courses after fellowship. Conclusion: The survey underlines the need to fill a gap in order to address the needs of young interventional cardiologists and it may serve as a starting point for developing tailored educational initiatives.